2017
DOI: 10.3354/ame01813
|View full text |Cite
|
Sign up to set email alerts
|

Versatile photophysiology of compositionally similar cyanobacterial mat communities inhabiting submerged sinkholes of Lake Huron

Abstract: Recently discovered submerged sinkholes in Lake Huron are high-sulfur, lowoxygen extreme environments for microbial life. In order to understand the relationship between the physical environment, photophysiology and community composition, we measured the physical conditions, photophysiological indices, and genetic diversity at 3 microbial mat sites bathed in high conductivity groundwater under a natural light gradient during 2012 and 2013. A strong seasonal trend prevailed at all sites, characterized by decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…In July 2016, much of the sediment–water interface (SWI) of the Middle Island Sinkhole (MIS) was dominated with surface coverings that were similar to those described in previous studies (Biddanda et al, 2006, 2015; Kinsman‐Costello et al, 2017; Nold et al, 2010, 2013; Ruberg et al, 2008; Snider et al, 2017; Voorhies et al, 2012): purple mats, gray sediment lacking cohesive mat, and intermittently observed white patches. We chose to focus on the two most commonly observed surface coverings to study diurnal δ 34 S patterns in porewater sulfide in 2016: the purple mats and gray sediment with diffuse mat at the SWI (i.e., gray mats) as two common end‐member environments (Figure 2).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…In July 2016, much of the sediment–water interface (SWI) of the Middle Island Sinkhole (MIS) was dominated with surface coverings that were similar to those described in previous studies (Biddanda et al, 2006, 2015; Kinsman‐Costello et al, 2017; Nold et al, 2010, 2013; Ruberg et al, 2008; Snider et al, 2017; Voorhies et al, 2012): purple mats, gray sediment lacking cohesive mat, and intermittently observed white patches. We chose to focus on the two most commonly observed surface coverings to study diurnal δ 34 S patterns in porewater sulfide in 2016: the purple mats and gray sediment with diffuse mat at the SWI (i.e., gray mats) as two common end‐member environments (Figure 2).…”
Section: Resultssupporting
confidence: 72%
“…Density stratification inhibits mixing with the overlying water, resulting in low‐oxygen (~2–4 mg/L) waters overlying the sediment–water interface (SWI; Ruberg et al, 2008). Light penetration to the SWI supports a dynamic microbial mat ecosystem (Biddanda et al, 2006, 2015; Grim, 2019; Kinsman‐Costello et al, 2017; Nold et al, 2010; Snider et al, 2017; Voorhies et al, 2012, 2016).…”
Section: Methodsmentioning
confidence: 98%
“…We shotgun sequenced white microbial mat communities that are bathed in similar groundwater at two contrasting locations: the library fountain in the town of Alpena, Michigan ( Figure 1A ; Snider et al, 2017 ) and the Isolated Sinkhole, which is submerged at a water depth of 93 m in Lake Huron ( Figure 1B ; Biddanda et al, 2006 ). The emerging groundwater at these two sites is sourced from the same Silurian-Devonian aquifer and has similar conductivity and chemistry ( Biddanda et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Groundwater seeps in this area also occur in sinkholes on land and at the Alpena County Library fountain, where an artesian well draws groundwater from the same aquifers that feed the sinkholes ( Snider et al, 2017 ). The fountain consists of a lower basin that has brown cyanobacterial mats and an upper basin that has white chemosynthetic mats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation